Analisis Efisiensi dan Efektivitas Pusat Pertanggungjawaban dalam Meningkatkan Kinerja Keuangan KPU Kota Magelang Tahun 2024 - Rifaa Fitria; Fiska Tiara Oktavianti Mendez; Defi Febrianti; Shoofii Arum Almirah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The purpose of this study is to examine the effectiveness of the responsibility center in improving the performance of the General Election Commission (KPU) of Magelang City. This study uses a quantitative descriptive analysis method using financial reports and performance reports of KPU Magelang City. The results show that the responsibility center can improve the efficiency and effectiveness of financial management of KPU Magelang City, thereby improving organizational performance. This study contributes to the development of a better financial management system and improves the performance of KPU Magelang City in holding democratic and transparent general elections.